Utilizing model-based systems engineering (MBSE) for tailoring an Islamic values-based sounding rocket development cycle - Alsudairi, Ahmad Nayef Salih; Mohd Rafie, Azmin Shakrine; Algarni, Abdullah Mohammad; Md Ali, Syaril Azrad; Gires, Ezanee; Abdullah, Amini Amir (The Aeronautical and Astronautical Society of the Republic of China, 2025)
This paper presents a novel life cycle model for developing university-scale sounding rockets, integrating technical and Islamic perspectives. The model, referred to as the 'Water Spring Model,' aims to align aerospace engineering processes with systems engineering (SE) phases and integrate Islamic values such as Itqan (perfection in work), Shura (consultation), and Jihad (intellectual struggle). The model was successfully applied in a small project that reached the simulation stage, providing a comprehensive framework connecting life cycle phases with the Aerospace Vehicle Design (AVD) process in a unified diagram. Despite the project’s limited scope, the model was found to be beneficial for fostering a holistic understanding among team members and connecting their work to motivating values. Feedback highlighted the need for improved governance, cross-departmental communication, and the integration of unified project models. Future work will detail the model’s processes and further integrate Tafsir and Fiqh methodologies. This initial application suggests that the model has potential for broader use in similar projects within Islamic countries, offering a balanced approach that enhances both project outcomes and team motivation.